2016
DOI: 10.2217/pme-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Microarray in Prenatal Diagnosis: Case Studies and Clinical Challenges

Abstract: Chromosomal microarray analysis (CMA) is a diagnostic tool used in the evaluation of pediatric patients with congenital anomalies or developmental and intellectual disability. In both the pediatric and prenatal patient population, CMA has been shown to have a higher detection rate of chromosomal abnormalities than conventional karyotype alone. Currently, the diagnostic yield of prenatal CMA is highest when applied to the evaluation of a fetus with multiple ultrasound anomalies. Challenges arise when CMA yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It has gradually replaced karyotyping in several countries for other indications too [82,[299][300][301]. The detection of submicroscopic CNVs allows the identification of a wider range of causes of malformations [302][303][304][305][306]. It represents a more standardized technique than karyotyping, being less prone to human errors.…”
Section: Chromosomal Microarray Analysismentioning
confidence: 99%
“…It has gradually replaced karyotyping in several countries for other indications too [82,[299][300][301]. The detection of submicroscopic CNVs allows the identification of a wider range of causes of malformations [302][303][304][305][306]. It represents a more standardized technique than karyotyping, being less prone to human errors.…”
Section: Chromosomal Microarray Analysismentioning
confidence: 99%
“…CMA allows the detection of small rearrangements that can underlie several structural anomalies [ 108 , 109 , 110 , 111 , 112 ]. This technique has largely replaced conventional karyotyping, becoming the first-tier genetic investigation after the detection of fetal structural anomalies in several countries, even if the most used approach (array-comparative genomic hybridization: a-CGH) is not able to identify balanced chromosomal aberrations, triploidies and mosaicisms below 30%.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although CMA has shown great values in prenatal diagnosis, this assay may detect VOUS, pathogenic CNVs in adulthood, and disease carriers. 35 Results from the NICHD trial showed that CMA identified 1.8% of the study fetuses with possible benign CNVs and 1.6% with possible pathogenic CNVs. 36 This VOUS may be attributed to rare or new CNVs, or due to variable penetrance.…”
mentioning
confidence: 92%